The Effect Of Work Environment, Work Stress And Motivation To Employee Engagement In Palm-Oil Industry (Study Case In Lambang Agro Plantation) - Democratio Luther; Alim Setiawan Slamet; Indra Refipal Sembiring (Jurnal Agribisnis Indonesia, 2026)
Labor is one of the factors that influences palm oil productivity. Good human resource (HR) management is necessary for efficiency, profitability, and company sustainability. Employee engagement (EE) combines attitudes, thoughts, and behaviors towards satisfaction, commitment, pride, loyalty, and responsibility. EE can be increased by paying attention to the work environment, stress, and motivation. This research examines the sway of the work environment, stress, and motivation on EE. The research was conducted at the head office of PT Lambang Agro Plantation in June – July 2025. The saturated sample (census) with 48 respondents determined the research sample. The data in this research uses primary data from interviews and questionnaires. Descriptive analysis is used to identify employee perceptions of the work environment, work stress, work motivation, and EE. The data was then analyzed using hierarchical regression with the help of Microsoft Excel and SPSS software. The findings suggest that good workplace has significant effect on EE for the first and second models, work stress has a negative and significant effect on EE in the second model, and work motivation has a positive and significant effect on EE in the third model. In contrast, the work environment and work stress do not significantly affect EE.